Design and Development of D‒α‒Tocopheryl Polyethylene Glycol Succinate‒block‒Poly(ε-Caprolactone) (TPGS−b−PCL) Nanocarriers for Solubilization and Controlled Release of Paclitaxel - Osman Yusuf; Raisuddin Ali; Abdullah H. Alomrani; Aws Alshamsan; Abdullah K. Alshememry; Abdulaziz M. Almalik; Afsaneh Lavasanifar; Ziyad Binkhathlan (Molecules, 2021)
The objective of this study was to synthesize and characterize a set of biodegradable block copolymers based on TPGS-block-poly(ε-caprolactone) (TPGS-b-PCL) and to assess their self-assembled structures as a nanodelivery system for paclitaxel (PAX). The conjugation of PCL to TPGS was hypothesized to increase the stability and the drug solubilization characteristics of TPGS micelles. TPGS-b-PCL copolymer with various PCL/TPGS ratios were synthesized via ring opening bulk polymerization of ε-caprolactone using TPGS, with different molecular weights of PEG (1–5 kDa), as initiators and stannous octoate as a catalyst. The synthesized copolymers were characterized using 1H NMR, GPC, FTIR, XRD, and DSC. Assembly of block copolymers was achieved via the cosolvent evaporation method. The self-assembled structures were characterized for their size, polydispersity, and CMC using dynamic light scattering (DLS) technique. The results from the spectroscopic and thermal analyses confirmed the successful synthesis of the copolymers. Only copolymers that consisted of TPGS with PEG molecular weights ≥ 2000 Da were able to self-assemble and form nanocarriers of ≤200 nm in diameter. Moreover, TPGS2000-b-PCL4000, TPGS3500-b-PCL7000, and TPGS5000-b-PCL15000 micelles enhanced the aqueous solubility of PAX from 0.3 µg/mL up to 88.4 ug/mL in TPGS5000-b-PCL15000. Of the abovementioned micellar formulations, TPGS5000-b-PCL15000 showed the slowest in vitro release of PAX. Specifically, the PAX-loaded TPGS5000-b-PCL15000 micellar formulation showed less than 10% drug release within the first 12 h, and around 36% cumulative drug release within 72 h compared to 61% and 100% PAX release, respectively, from the commercially available formulation (Ebetaxel®) at the same time points. Our results point to a great potential for TPGS-b-PCL micelles to efficiently solubilize and control the release of PAX.